Behavioral Economics and Public Sector Reform : An Accidental Experiment and Lessons from Cameroon - Raballand, Gaël; Rajaram, Anand (World Bank, Washington, DC, 2013)
Starting with the hypothesis that behaviors are the critical (and often overlooked) factor in public sector performance, this paper explores the notion of how behavioral change (and thus institutional change) might be better motivated in the public sector. The basis for this study is "an accidental experiment" resulting from the World Bank's operational engagement in Cameroon. In 2008, World Bank staff successfully concluded preparation on a project to support the Government of Cameroon to improve transparency, efficiency, and accountability of public finance management. The US$15 million project supported a number of ministries to strengthen a broad range of management systems and capacities. Independently and concurrently, other Bank staff initiated a low-profile, technical assistance project to improve performance in Cameroon's Customs, supported by a small trade facilitation grant of approximately US$300,000. One approach appears to have succeeded in initiating change while the other has signally failed. The two projects of different scale, scope and design in the same governance environment offer a very interesting natural experiment (unplanned but accidental for that reason) that allows insights into the nature of institutional change and the role of behavior and incentives and approaches that offer greater prospects for making reform possible. The paper confirms the value of using ideas from behavioral economics, both to design institutional reforms and to critically assess the approach to institutional reform taken by development agencies such as the World Bank.